2016
DOI: 10.3409/fb64_3.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prebiotics and Synbiotics Delivered <I>In Ovo</I> on Broiler Small Intestine Histomorphology During the First Days After Hatching

Abstract: Effects of prebiotics and synbiotics delivered in ovo on broiler small intestine histomorphology during the first days after hatching. Folia Biologica (Kraków) 64: 131-143. The objective of the study was to determine the effect of prebiotics and synbiotics administered in ovo on the 12 th day of incubation, on the development of the intestinal villi and the number of goblet cells in the small intestine of broiler chickens on the 1 st and the 4 th days of life of chicks. Two prebiotics: inulin (PI) or Bi 2 tos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
(63 reference statements)
2
22
0
1
Order By: Relevance
“…The number of microorganisms in sections of the digestive system can vary significantly 49 . On the first day, coli group bacteria, enterococci and lactic bacteria predominate in the chicken goiter, duodenum and small intestine 50,51 . Their initial count is low, but already after 5-6 hours it ranges between 10 9 and 10 10 CFU g −1 of the excreta.…”
Section: Discussionmentioning
confidence: 99%
“…The number of microorganisms in sections of the digestive system can vary significantly 49 . On the first day, coli group bacteria, enterococci and lactic bacteria predominate in the chicken goiter, duodenum and small intestine 50,51 . Their initial count is low, but already after 5-6 hours it ranges between 10 9 and 10 10 CFU g −1 of the excreta.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that microvillus height in the jejunum and ileum and the ratio of villus to crypt depth in the ceca were increased by FOS ( 40 , 41 ). Bogucka et al ( 92 ) also reported that in ovo injection of inulin increased villus height in broilers at the first day after hatching. In addition, the use of inulin could increase jejunal mucin mRNA expression to produce more mucin, protecting intestinal epithelial cells in broilers ( 39 ).…”
Section: Fructansmentioning
confidence: 92%
“…During in ovo stimulation, a prebiotic or synbiotic is injected into the air cell of the incubating egg (in this study, on day 12 of egg incubation) and stimulates the development of indigenous microbiota prior to hatching [31]. The prebiotic supplementation at the embryonic stage supports not only the microbiota development in the growing chickens [32][33][34] but also improves the immune system [35,36], gut morphology [37] and the intestinal barrier function [32].…”
Section: Introductionmentioning
confidence: 99%